Cripto-1: an extracellular protein – connecting the sequestered biological dots. (3rd September 2015) - Klauzinska, Malgorzata; Bertolette, Daniel; Tippireddy, Sudhamsh; Strizzi, Luigi; Gray, Peter C.; Gonzales, Monica; Duroux, Meg; Ruvo, Menotti; Wechselberger, Christian; Castro, Nadia P.; Rangel, Maria Cristina; Focà, Annalia; et al.
Abstract: Cripto-1 (CR-1) is a multifunctional embryonic protein that is re-expressed during inflammation, wound repair, and malignant transformation. CR-1 can function either as a tethered co-receptor or shed as a free ligand underpinning its flexible role in cell physiology. CR-1 has been shown to mediate cell growth, migration, invasion, and induce epithelial to mesenchymal transition (EMT). The main signaling pathways mediating CR-1 effects include Nodal-dependent (Smad2/3) and Nodal-independent (Src/p44/42/Akt) signaling transduction pathways. In addition, there are several naturally occurring binding partner proteins (BPPs) for CR-1 that can either agonize or antagonize its bioactivity. We will review the collective role of CR-1 as an extracellular protein, discuss caveats to consider in developing a quantitation assay, define possible mechanistic avenues applicable for drug discovery, and report on our experimental approaches to overcome these problematic issues.